2014
DOI: 10.1099/mic.0.076463-0
|View full text |Cite
|
Sign up to set email alerts
|

Enhanced expression of Bacillus subtilis yaaA can restore both the growth and the sporulation defects caused by mutation of rplB, encoding ribosomal protein L2

Abstract: A temperature-sensitive mutation in rplB, designated rplB142, encodes a missense mutation at position 142 [His (CAT) to Leu (CTT)] of Bacillus subtilis ribosomal protein L2. The strain carrying the mutation grew more slowly than the wild-type, even at low temperatures, probably due to the formation of defective 70S ribosomes and the accumulation of incomplete 50S subunits (50S* subunits). Gel analysis indicated that amounts of L2 protein and also of L16 protein were reduced in ribosomes prepared from the rplB1… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
19
1

Year Published

2014
2014
2021
2021

Publication Types

Select...
5
2

Relationship

3
4

Authors

Journals

citations
Cited by 13 publications
(20 citation statements)
references
References 50 publications
0
19
1
Order By: Relevance
“…Nonetheless, S. pneumoniae SP_0007 peaked with the 50S proteins, supporting the prediction of a conserved role in 50S recycling. On the contrary, S4 domain protein SP_2226, whose Bacillus subtilis homolog YaaA was proposed to be involved in 50S assembly (Suzuki et al , ), co‐migrated primarily with the 30S proteins, therefore suggesting that it is involved in a different part of ribosomal biology than originally predicted. C‐termini of different lengths in Streptococcus , Bacillus, and Staphylococcus species (Appendix Fig S3) may alter the interactomes of these homologous proteins.…”
Section: Resultsmentioning
confidence: 95%
“…Nonetheless, S. pneumoniae SP_0007 peaked with the 50S proteins, supporting the prediction of a conserved role in 50S recycling. On the contrary, S4 domain protein SP_2226, whose Bacillus subtilis homolog YaaA was proposed to be involved in 50S assembly (Suzuki et al , ), co‐migrated primarily with the 30S proteins, therefore suggesting that it is involved in a different part of ribosomal biology than originally predicted. C‐termini of different lengths in Streptococcus , Bacillus, and Staphylococcus species (Appendix Fig S3) may alter the interactomes of these homologous proteins.…”
Section: Resultsmentioning
confidence: 95%
“…In fact, it has been reported that incorporation of L16 induces a strong conformational change in 50S particles and influences the association of the ribosomal subunits (64,65). Similarly, we have reported recently that the H142L mutation in ribosomal protein L2 not only reduces the efficiency of formation of the 70S ribosome but also leads to a deficiency of L16 in the 50S subunit (48). Therefore, it seems that the defect in formation of the 70S ribosome in the ⌬rpmH mutant is probably due to conformational changes in the 50S subunit that are caused by lack of L34 followed by a reduction in the binding affinity of L16.…”
Section: Discussionmentioning
confidence: 93%
“…30S and 50S ribosomal subunits were prepared from wild-type and ⌬rpmH mutant cells grown in LB at 37°C. The preparation of small and large subunits and association experiments were performed as described previously with a slight modification (48). Briefly, the S30 fraction prepared from wild-type cells cultivated to exponential phase (OD 600 , ϳ0.4) was centrifuged at 65,000 ϫ g at 4°C for 17 h through a 10 to 40% sucrose gradient in buffer B (20 mM Tris-HCl, pH 7.6, 100 mM CH 3 COONH 4 , 0.1 mM dithiothreitol [DTT], and 2 mM phenylmethylsulfonyl fluoride [PMSF]) that contained 1 mM (CH 3 COO) 2 Mg in a Hitachi P28SA rotor to separate the 30S and 50S subunits.…”
Section: Methodsmentioning
confidence: 99%
“…To replace the cat gene of strain RIK1141 (DtrpB9A9 :: P rrnO -cat erm181 trpC2) (Akanuma et al, 2006;Yano et al, 2013) with the lacZ gene, the upstream and downstream regions of the cat gene in the RIK1140 chromosome (DtrpB9A9 :: P rrnO -cat erm trpC2) (Yano et al, 2013) were amplified using oligonucleotide primer combinations PrLacUF/PrLacUR and PrLacDF/PrLacDR, respectively. Next, the lacZ gene of RIK3106 (trpC2 amyE :: P yaaAwt -lacZ cat) (Suzuki et al, 2014) was amplified by PCR using the primers PrLacLF and PrLacLR. In another PCR, all three above-mentioned amplified fragments were used as the DNA template, and the PCR amplification reaction was carried out using the primers PrLacUF and PrLacDR.…”
mentioning
confidence: 99%